The canary in the coal decline: Appalachian household finance and the transition from fossil fuels - Blonz, Joshua; Roth Tran, Brigitte; Troland, Erin (Journal of Financial Economics, 2026)
We use individual-level credit data to study how recent declines in Appalachian coal mining affected household finances between 2011 and 2018. Using exogenous variation in electricity sector demand for coal, we find declines in coal demand decreased credit scores and increased financial distress within two years of coal shocks. These effects cannot be explained solely by job losses in coal mine worker households. Credit score declines and financial distress were largest among older individuals and people with lower-middle credit scores. Our results suggest the transition away from fossil fuels may impose meaningful costs on other fossil fuel extraction communities.